Intra-Testicular Signals Regulate Germ Cell Progression and Production of Qualitatively Mature Spermatozoa in Vertebrates - Meccariello, Rosaria; Chianese, Rosanna; Chioccarelli, Teresa; Ciaramella, Vincenza; Fasano, Silvia; Pierantoni, Riccardo; Cobellis, Gilda (Frontiers in Endocrinology, 2014)
Spermatogenesis, a highly conserved process in vertebrates, is mainly under the hypothalamic–pituitary control, being regulated by the secretion of pituitary gonadotropins, follicle stimulating hormone, and luteinizing hormone, in response to stimulation exerted by gonadotropin releasing hormone from hypothalamic neurons. At testicular level, gonadotropins bind specific receptors located on the somatic cells regulating the production of steroids and factors necessary to ensure a correct spermatogenesis. Indeed, besides the endocrine route, a complex network of cell-to-cell communications regulates germ cell progression, and a combination of endocrine and intra-gonadal signals sustains the production of high quality mature spermatozoa. In this review, we focus on the recent advances in the area of the intra-gonadal signals supporting sperm development.